Seismic P Wave Velocity Model From 3‐D Surface and Borehole Seismic Data at the Alpine Fault DFDP‐2 Drill Site (Whataroa, New Zealand). Issue 4 (12th April 2020) - Lay, V.; Buske, S.; Bodenburg, S. B.; Townend, J.; Kellett, R.; Savage, M. K.; Schmitt, D. R.; Constantinou, A.; Eccles, J. D.; Bertram, M.; Hall, K.; Lawton, D.; et al.
Abstract: The New Zealand Alpine Fault is a major plate boundary that is expected to be close to rupture, allowing a unique study of fault properties prior to a future earthquake. Here we present 3‐D seismic data from the DFDP‐2 drill site in Whataroa to constrain valley structures that were obscured in previous 2‐D seismic data. The new data consist of a 3‐D extended vertical seismic profiling (VSP) survey using three‐component and fiber optic receivers in the DFDP‐2B borehole and a variety of receivers deployed at the surface. The data set enables us to derive a detailed 3‐D P wave velocity model by first‐arrival traveltime tomography. We identify a 100–460 m thick sediment layer (mean velocity 2, 200 ± 400 m/s) above the basement (mean velocity 4, 200 ± 500 m/s). Particularly on the western valley side, a region of high velocities rises steeply to the surface and mimics the topography. We interpret this to be the infilled flank of the glacial valley that has been eroded into the basement. In general, the 3‐D structures revealed by the velocity model on the hanging wall of the Alpine Fault correlate well with the surface topography and borehole findings. As a reliable velocity model is not only valuable in itself but also crucial for static corrections and migration algorithms, the Whataroa Valley P wave velocity model we have derived will be of great importance for ongoing seismic imaging. Our results highlight the importance of 3‐D seismic data for investigating glacial valley structures in general and the Alpine Fault and adjacent structures in particular. Key Points: Vertical seismic profile (VSP) and 3‐D surface seismic data characterize the DFDP‐2 drill site near the Alpine Fault in the Whataroa Valley The tomographic P wave velocity model reveals the 3‐D structure of the glacial valley to 1‐km‐depth and is consistent with gravity models P wave velocities correlate well with surface topographic features and drilling logs